Concentração de flúor nas águas de abastecimento público de municípios da região noroeste do estado de São Paulo, Brasil - Saliba, Nemre Adas [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Tiano, Ana Valéria Pagliari [UNESP] (FapUNIFESP (SciELO), 2006)
It may be difficult for small and medium cities to obtain information about the fluoride content of public water, because of the lack of equipments and technicians. This study aimed to analyze the fluoride levels of the water supplied by the public treatment stations of 40 cities situated in the northwest region of São Paulo State, during a period of 6 months, to verify if fluoridation occurs in a continuous manner and if the fluoride levels are within the recommended. Maps of the water distribution system were obtained from the water treatment companies and utilized to randomize the addresses of the collection sites, so that they included all regions with treated water sources. One water sample by month was collected and analyzed in duplicate using an ion-specific-electrode. Samples with 0.6 to 0.8 mgF/L were considered acceptable. In the 38 cities that regularly provided the samples in the 6 months of the study, water from 144 collection sites was collected and a total of 864 samples were analyzed, of which 61.81 percent were classified as unacceptable. It was observed that 33 cities performed fluoridation but in 78.79 percent of these cities there were variations in the fluoride level among the sites and in the same site during the period of study. One can conclude that most of these cities do not control the fluoride levels in the public water, since fluoridation occurs in a discontinuous manner and in most of the situations not within the recommended concentrations.
Fluoride level in public water supplies of cities from the northwest region of São Paulo State, Brazil
Keywords: Fluoride; Oral health; Systemic fluoridation; Water fluoridation